ChemInform Abstract: Possible Superhardness of CrB4. Issue 14 (20th March 2013) - Knappschneider, Arno; Litterscheid, Christian; Dzivenko, Dmytro; Kurzman, Joshua A.; Seshadri, Ram; Wagner, Norbert; Beck, Johannes; Riedel, Ralf; Albert, Barbara
Abstract The single crystal structure refinement of CrB4 is repeated and it is confirmed that the compound crystallizes in the orthorhombic space group Pnnm with Z = 2.